Determination of antibodies against Neospora caninum in water buffaloes (Bubalus bubalis) in the Peruvian Amazonia - Jara V., Javier (2011)
Neosporosis is an important parasitic disease that causes reproductive problems as abortion and neonatal mortality in diary cattle. The aim of the study was to determine the presence of antibodies against Neospora caninum in water buffaloes reared in five farms located in Jenaro Herrera district, Loreto, Peru in 2008. Blood samples were collected from 83 female dairy buffalo older than 2 years. Serum samples were tested by indirect ELISA and immunnefluorescent antibody test (IFAT). None of sera presented antibodies against N. caninum to the dilution 1:25 and 1:100 using indirect ELISA or to the dilution 1:100 by IFAT. The results suggest a low exposition of water buffaloes to N. caninum in the studied area.